Design Of Department Performance Efficiency Measurement At Higher Education With Integration Of Balanced Scorecard (Bsc) And Data Envelopment Analysis (Dea) Approach (Universitas Esa Unggul, 2011)
AbstractThis research discusses the design of department performance efficiency measurement at higher education. Performance measurement is generally a basis for decision making should reflect information such as efficiency, effectiveness and productivity. In this study the set of input and output, grouped by the perspective of the Balanced Scorecard (BSC). By using Data Envelopment Analysis (DEA), the relative efficiency of the department can be known. Totaly there are 5 input and 9 output that become parameters for measuring performance of department in higher education. Based on the BSC perspectives, financial get 2 inputs-2 outputs, internal business process get 1 input-2 output, customer get 1 input-3 output, finally, learning and growth get 1 input-2 output.Keywords: Balanced Scorecard, Data Envelopment Analysis, Performance Measurement